1973
DOI: 10.1111/j.1699-0463.1973.tb03546.x
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Cancer

Abstract: In order to elucidate the question of whether or not gynecomastia is a premalignant state, a Danish series comprising 265 cases of male breast cancer was reviewed with regard to a previous history of gynecomastia and the finding of clinical gynecomastia on admission. Furthermore, preparations from 187 cases of the same series were assessed with a view to the presence of histologically verified gynecomastia. In 10 patients there was a history of gynecomastia; only one patient presented clinical gynecomastia on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…No further management is necessary if the tumor is locally limited without lymph nodes involvement or distant metastases (Scheike -1975). The initial treatment combines local excision and a palliative radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…No further management is necessary if the tumor is locally limited without lymph nodes involvement or distant metastases (Scheike -1975). The initial treatment combines local excision and a palliative radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The most common presentations are painless palpable mass, skin ulceration, and nipple retraction or discharge in approximately 75% of the cases, similar to women (7,(50)(51)(52)(53). Since the breast tissue in men is undersized, the nipple is mostly involved at early stages.…”
Section: Symptoms Clinical Signs and Manifestationsmentioning
confidence: 99%
“…The staging of the disease during presentation is as follows on the basis of the Tumor-Node-Metastasis (TNM) system presented by the largest case series in the literature: Stage 1: 37%, stage II: 21%, stage III: 33%, stage IV: 9% (51,52,60,61). While the period between disease onset and diagnosis was 29 months in the past (62), this period has been reduced to 6 months in the newer series (63).…”
Section: Symptoms Clinical Signs and Manifestationsmentioning
confidence: 99%
“…Some additional breast malignancies described in men were infl ammatory, lobular, papillary, ductal cancer in situ, and atypical hyperplasia of ductal epithelium (Giordano et al 2004 ). Some observations of tubular cancer characterized with high differentiation and good prognosis were published (Scheike 1975 ). Single instances of breast sarcomas in men were described.…”
Section: Epidemiology Etiology Development and Prognosismentioning
confidence: 99%
“…Approximately 18-54 % of patients develop remote metastases after the treatment of local types of cancer (Scheike 1975 ;Ostrovskaya et al 1988 ;Letyagin 2006 ;Contractor et al 2008 ;Korde et al 2010 ). Based on studies of invasion of breast carcinoma into blood vessels, Akimov ( 1992 ) reported that the incidence is less in men than in women (9.1 % vs. 15.3 %, respectively).…”
Section: Distant Metastasesmentioning
confidence: 99%